ANALISIS POTENSI ENERGI MATAHARI MENJADI ENERGI LISTRIK DI INDONESIA: PROYEKSI DAN PERAMALAN KAPASITAS TERPASANG PLTS DENGAN METODE DOUBLE EXPONENTIAL SMOOTHING - Timotius, Hizkia; Welman Simatupang, Joni; Andriani, Mutiara; Situmeang, Praja; Ramos SM, Indra; Fauzi, Muamar (TESLA: Jurnal Teknik Elektro, 2023)
This study endeavors to assess the progression in the installed capacity of Solar Power Plants (PLTS) in Indonesia, given that the obtained data indicates a solar energy potential of 207,898 MW in the country. However, the installed capacity of Solar Photovoltaic (PV) Power Plants (PLTS) is still low compared to other types of power plants. In the projection for the National Electricity Supply Business Plan (RUPTL) 2021-2030, it is expected that the installed capacity of PLTS will increase to 4.7 GWp by 2030, but this is still far from the target projection of 800-840 GWp by 2050 according to IRENA. Through forecasting using three methods, namely moving average, single exponential smoothing, and double exponential smoothing, the projected installed capacity for the year 2050 significantly deviates from IRENA's projection. Historical data of installed capacity of PLTS from 2010 to 2022 was used as the basis for the forecasting. The results of the three forecasting methods were compared to assess their accuracy and performance in predicting the installed capacity of PLTS in the future years. This study suggests using the double exponential smoothing method as a feasible forecasting technique and emphasizes the need for further research on inhibiting factors and support from various stakeholders to successfully utilize solar energy as a source of electricity in Indonesia. The findings of this research provide guidance for the planning and development of PLTS in the future, as well as important implications for achieving the national renewable energy projection targets. ABSTRAK: Studi ini berupaya untuk menilai perkembangan kapasitas terpasang Pembangkit Listrik Tenaga Surya (PLTS) di Indonesia mengingat data yang diperoleh menunjukkan potensi energi surya sebesar 207.898 MW di Indonesia. Namun, kapasitas terpasang Pembangkit Listrik Tenaga Surya (PLTS) masih rendah dibandingkan jenis pembangkit lainnya. Dalam proyeksi RUPTL 2021-2030, diharapkan kapasitas terpasang PLTS meningkat menjadi 4,7 GWp pada tahun 2030, tetapi tetap jauh dari target proyeksi IRENA yang mencapai 800-840 GWp pada tahun 2050. Melalui peramalan menggunakan tiga metode, yaitu moving average, single exponential smoothing, dan double exponential smoothing, diperoleh hasil kapasitas terpasang pada tahun 2050 dengan selisih yang signifikan dari proyeksi IRENA. Data historis kapasitas terpasang PLTS dari tahun 2010 hingga 2022 diambil sebagai dasar peramalan. Hasil peramalan dari ketiga metode tersebut dibandingkan untuk menilai akurasi dan kinerjanya dalam memprediksi kapasitas terpasang PLTS pada tahun-tahun mendatang. Penelitian ini menyarankan penggunaan metode double exponential smoothing sebagai metode peramalan yang layak, dan menekankan perlunya penelitian lebih lanjut mengenai faktor penghambat dan dukungan dari berbagai pihak untuk berhasilnya pemanfaatan energi surya sebagai sumber tenaga listrik di Indonesia. Hasil penelitian ini memberikan panduan untuk perencanaan dan pengembangan PLTS di masa depan, serta implikasi penting dalam mencapai target proyeksi energi terbarukan nasional.